BigData - Data to Insight - Mohanty, Amarendra; D.Venkata Subramanian, Dr. (International Journal of Engineering and Technology, 2026)
Sign language is a language that uses manual communication to convey meaning. This includes simultaneously employing hand gestures, movement, orientation of the fingers, arms or body, and facial expressions. RASPBOT has been designed to understand not only human voice but hand signs language as well. It has been designed in such a way that it can be used by a wide variety of individuals. RASPBOT allows the users to: Ask a question normally or ask a question using sign language. RASPBOT recognizes the Hand Signs and produces the recognized Alphanumeric Character as output. It forms meaningful sentences and give responses to the queries by recognizing the characters thus breaking down the barriers between normal people and specially disabled people. These features have been represented by functions in the program. RASPBOT then understands the question and then replies appropriately.
Keywords: Chatbot; RNN; Convolutional Neural Networks; Sign Language; Deep Learning..